Who Shall Succeed? How CEO/Board Preferences and Power Affect the Choice of New CEOs - Zajac, Edward J.; Westphal, James D. (Academy of Management Journal, 1996)
This study shows how social psychological and sociopolitical factors can create divergence in the preferences of an incumbent CEO and existing board regarding the desired characteristics of a new CEO, and how relative CEO/board power can predict whose preferences are realized. Using extensive longitudinal data, we found that more powerful boards are more likely to change CEO characteristics in the direction of their own demographic profile. Outside successors are also typically demographically different from their CEO predecessors but demographically similar to the boards.